2018
DOI: 10.1017/s1463423618000361
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the attitudes and views of general practitioners on the use of video consultations in a primary healthcare setting: a qualitative pilot study

Abstract: GPs did see potential benefits to using video consultations but also expressed concerns that need to be addressed if they are to have full confidence in the system. The views of those who are going to use video consultation as a means of increasing patient access are paramount if such tools are to be a core part of primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 12 publications
(18 reference statements)
2
58
0
1
Order By: Relevance
“…20,25 While there is evidence that patients and clinicians consider VC as a potentially acceptable method of consultation with a primary care clinician, much of this is based on hypothetical opinion rather than experience. [26][27][28][29] Overall, it is not currently clear whether the perceived benefits and concerns are realised in practice for primary care settings. Research conducted in secondary care settings has shown that implementation of VCs into real-world settings is complex and context dependent.…”
Section: Introductionmentioning
confidence: 99%
“…20,25 While there is evidence that patients and clinicians consider VC as a potentially acceptable method of consultation with a primary care clinician, much of this is based on hypothetical opinion rather than experience. [26][27][28][29] Overall, it is not currently clear whether the perceived benefits and concerns are realised in practice for primary care settings. Research conducted in secondary care settings has shown that implementation of VCs into real-world settings is complex and context dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians can often be the biggest barrier to implementation, being resistant to change as a result of numerous influencing factors, having hesitations towards the quality of the patient interactions and being apprehensive of any technical difficulties. 11,16 It is likely that dental teams will have hesitation and questions regarding a video consultation solution; examples are highlighted in Figure 1. Information governance regulations may cause clinicians to be anxious towards the privacy of real-time interactive video consultations.…”
Section: Limitationsmentioning
confidence: 99%
“…Considerations also need to be given to the image quality, the reliability of internet connection and patient factors such as ability to connect to the software delivering real-time interactive video consultations, lighting, manual dexterity, familiarity with mobile/tablet devices and the technology literacy of the service user to utilise technology-based consultations. 11 There is, however, the ability to assess (to an extent) extraoral and intraoral swellings, grossly carious teeth, soft tissue lesions, mobile teeth, fractured prosthodontic work and orthodontic emergencies (Table 1). Additionally, the limitation of poor image quality and access could be mitigated through a combined approach, utilising real-time video with a 'store-and-forward' (asynchronous) approach.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations